AN ANALYSIS OF THE ROLE OF JUDICIARY AND JUDICIAL INDEPENDENCE IN PAKISTAN - Madiha Abbas; Dr. Mushtaque Ali Abbasi; Ume Raqia (International Journal of Contemporary Issues in Social Sciences, 2024)
The institution of judiciary is the cornerstone of democracy. Judiciary is the guardian of Constitution. This article aims to provide insights into the evolution of judiciary in Pakistan. It will highlight the role and function of judiciary. With the help of an insignificant study of history and functioning of judiciary this article also aims to explore the judicial independence in the Pakistan. Judicial independence is the requisite of the rule of law. In this article a glimpse of historical background will help to have an in-depth and meticulous research on the judicial independence, role and functioning of judiciary in Pakistan. This article will highlight the role of judiciary in maintaining rule of law, rights of individuals and also the challenges faced by the judiciary in Pakistan. Moreover, it will proved a significant literature for further study in the area of political history of Pakistan.